let x=1+a+a2+.............. y=1+b+b2+.......... thn prove that

1+ab+a2b2+.......=xy/x+y-1

Given, x=1+a+a2+......Since this is a infinite G.P. series, where, (first term)=1 and common difference=a,So,x=11-ax-ax=1ax=x-1a=x-1xSimilarly,y=1+b+b2+...... is a infinite G.P. series, where, (first term)=1 and common difference=b,So,y=11-by-by=1by=y-1b=y-1yAnd now,L.H.S.=1+ab+a2b2+....            =11-ab    infinte G.P. series where (first term)=1 and common difference=ab             =11-x-1xy-1y            =xyxy-xy+x+y-1            =xyx+y-1            =R.H.S.Hence Proved.

  • 135
What are you looking for?